2012
DOI: 10.1007/s00198-012-1898-9
|View full text |Cite
|
Sign up to set email alerts
|

Heel bone mass of a young South Indian population with a Nigerian population residing in a South Indian suburban neighborhood: a comparative study

Abstract: Peak bone strength was dominant in the Nigerian population compared to that of Indians. The Indian population is approximately lagging by 28-30% with respect to peak bone mass behind their Nigerian equivalents. Indian non-vegetarian male and female populations lagged by 6.15% and 6.16% behind the Indian vegetarian male and female populations, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…65 Unadjusted BMD data were not reported for 1 study. 66 Nine additional studies were excluded from this systematic review and meta-analysis because LS, FN, or WB BMD data were not presented; 5 of these studies measured BMD at the calcaneum, 61,[67][68][69][70] 3 measured it at the radius (mid and distal), [71][72][73] and 1 measured it at the proximal phalanx of the third finger. 74 Consequently, the final sample consisted of 20 articles (15 including BMD and 5 including fracture rate data) ( Figure 1).…”
Section: Search Summarymentioning
confidence: 99%
“…65 Unadjusted BMD data were not reported for 1 study. 66 Nine additional studies were excluded from this systematic review and meta-analysis because LS, FN, or WB BMD data were not presented; 5 of these studies measured BMD at the calcaneum, 61,[67][68][69][70] 3 measured it at the radius (mid and distal), [71][72][73] and 1 measured it at the proximal phalanx of the third finger. 74 Consequently, the final sample consisted of 20 articles (15 including BMD and 5 including fracture rate data) ( Figure 1).…”
Section: Search Summarymentioning
confidence: 99%
“…Sapthagirivasan et al showed that the bone mass reached its peak value in young Indian men whose age ranges from 26 to 30 years. They also compared the heel BMD with BMI and weight which shows the statistically significant value (p<0.01) [23]. In this study, the body weight and BMI showed a significant difference (p<0.05) with LC-BMD in Indian men, whereas in Nepal-Bhutan population, it showed a significant difference with LC-BMD (p<0.05) and with RC-BMD (p<0.01).…”
Section: Kumar Et Almentioning
confidence: 55%
“…The rate of bone loss depends on race, gender, geographical location and age. Studies have proven that black women possess superior bone quality than Asian counterparts and seldom incur severe bone loss (Sapthagirivasan and Anburajan, 2012). Though the loss of bone quality on ageing is observed in men, the severity is minimal compared to equivalent females.…”
Section: Introductionmentioning
confidence: 99%